The changing clinical landscape in acupuncture for women's health: a cross-sectional online survey in New Zealand and Australia - Sandro Graca; Debra Betts; Kate Roberts; Caroline A. Smith; Mike Armour (BMC, 2022)
Abstract Background Acupuncture is a popular treatment for women's health. Several trials and meta-analysis have been published in recent years on key women's health conditions but it is unclear if this has led to any changes in clinical practice or referrals from other health professionals. The aim of this survey was to explore if, how, and why, aspects of acupuncture practice have changed since our survey in 2013. Method An online cross-sectional survey of registered acupuncturists and Chinese Medicine practitioners in Australia and New Zealand. Questions covered the practitioner demographics and training, women's health conditions commonly treated, modalities used, sources of information and continuing education (CE) (e.g. webinars), changes in clinical practice, and referral networks. Results One hundred and seventy registered practitioners responded to this survey, with 93% reporting treating women's health in the last 12 months. The majority of respondents were from Australia (60%), held a bachelors level qualification (60%), and used a traditional Chinese medicine framework (86%). Most practitioners incorporated other modalities in addition to acupuncture. Most practitioners' referral networks were predominantly based on word of mouth for menstrual, fertility and pregnancy related conditions, with referrals from medical practitioners being much less common. More than half (57%) reported having changed their women's health practice in the past 12 months; just over a quarter of those who changed treatment (27%) reported it was due to research findings. The most commonly used sources of information/CE used to inform treatment were webinars and conferences, while peer-reviewed journal articles were the least commonly used source. Conclusion Acupuncture practitioners in Australia and New Zealand commonly treat women's health conditions, but this is usually the result of women seeking them out, rather than being referred from a medical practitioner. The majority of practitioners did report changing their women's health practice, but peer reviewed academic articles alone are not an ideal medium to convey this information since practitioners favour knowledge obtained from webinars and conferences. Academics and other clinician researchers should consider alternative means of disseminating knowledge beyond traditional academic publications and conferences, special interest groups may assist in this and also help improve research literacy.